2012
DOI: 10.1136/bcr-2012-006872
|View full text |Cite
|
Sign up to set email alerts
|

Giant tuberculoma in an adolescent: atypical form of tuberculosis

Abstract: SummaryA tuberculoma is a rare form of presentation of tuberculosis (TB) in children. We describe the case of a 13-year-old girl, with 3 weeks of progressive tiredness and asthenia and a 48 h fever and cough. Physical examination revealed diminished pulmonary sounds in the left lower hemithorax. A chest radiograph showed an oval hypotransparency image in this location. The TB skin test was anergic and sputum was negative for acid-fast bacilli (AFB). The thoracic CT revealed a cystic mass in the left lower half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Even with bronchoscopy, lavage samples are often not collected from the lesion. 1,4 Concerning the imaging diagnosis, chest radiography can also fail to detect these lesions, requiring a chest-CT. 1,4 Diagnosis confirmation frequently requires invasive procedures such as percutaneous needle aspiration or thoracotomy. 1 In these cases, anti-bacillar treatment was sufficient for significant size reduction, but surgery may be necessary in some cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even with bronchoscopy, lavage samples are often not collected from the lesion. 1,4 Concerning the imaging diagnosis, chest radiography can also fail to detect these lesions, requiring a chest-CT. 1,4 Diagnosis confirmation frequently requires invasive procedures such as percutaneous needle aspiration or thoracotomy. 1 In these cases, anti-bacillar treatment was sufficient for significant size reduction, but surgery may be necessary in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…1,4 Concerning the imaging diagnosis, chest radiography can also fail to detect these lesions, requiring a chest-CT. 1,4 Diagnosis confirmation frequently requires invasive procedures such as percutaneous needle aspiration or thoracotomy. 1 In these cases, anti-bacillar treatment was sufficient for significant size reduction, but surgery may be necessary in some cases. 1 Treatment duration is not well stablished and is often a dilemma, given that tuberculomas may persist after treatment and continue to decrease for several months before complete resolution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tuberculosis might manifest in an unusual way and imitate other lung disease entities. Mascarenhas et al [6] reported an unusual case of a giant tuberculoma in an adolescent. A 13-year-old girl had in her chest a large cystic lesion that was initially treated as a hydatid cyst.…”
Section: Discussionmentioning
confidence: 99%